High-resolution satellite turbidity and sea surface temperature observations of river plume interactions during a significant flood event - V. E. Brando; F. Braga; L. Zaggia; C. Giardino; M. Bresciani; E. Matta; D. Bellafiore; C. Ferrarin; F. Maicu; A. Benetazzo; D. Bonaldo; F. M. Falcieri; et al. (Ocean Science, 2015)
Sea surface temperature (SST) and turbidity (T) derived from Landsat 8 (L8) imagery were used to characterize river plumes in the northern Adriatic Sea (NAS) during a significant flood event in November 2014. Circulation patterns and sea surface salinity (SSS) from an operational coupled ocean-wave model supported the interpretation of the plumes' interaction with the receiving waters and among them. There was a good agreement of the SSS, T, and SST fields at the sub-mesoscale and mesoscale delineation of the major river plumes. L8 30 m resolution also enabled the description of smaller plume structures. The different plumes' reflectance spectra were related to the lithological fingerprint of the sediments in the river catchments. Sharp fronts in T and SST delimited each single river plume. The isotherms and turbidity isolines' coupling varied among the plumes due to differences in particle loads and surface temperatures in the discharged waters. The surface expressions of all the river plumes occurring in NAS were classified based on the occurrence of the plume dynamical regions in the L8 30 m resolution imagery.

Investigation of saline water intrusions into the Curonian Lagoon (Lithuania) and two-layer flow in the Klaipėda Strait using finite element hydrodynamic model - P. Zemlys; C. Ferrarin; G. Umgiesser; S. Gulbinskas; D. Bellafiore (Ocean Science, 2013)
This work is focused on the application of a modelling system to simulate 3-D interaction between the Curonian Lagoon and the Baltic Sea coastal waters and to reflect spatiotemporal dynamics of marine waters in the Curonian Lagoon. The model system is based on the finite element programme package SHYFEM which can be used to resolve the hydrodynamic equations in lagoons, coastal seas, estuaries and lakes. The results of a one year (2009) 3-D model simulation with real weather and hydrological forcing show that the saline water intrusions from the sea through Klaipėda Strait are gradually decreasing with distance from the sea and become negligible (average annual salinity about 0.57‰) at a distance of about 20 km to the south of Kiaulės Nugara island. Analyses of the simulation results also show this area to be highly heterogeneous according to the vertical salinity distribution. While in the deeper Klaipėda Strait (harbour waterway) differences in average salinity between near bottom and surface layers varies in the range 2–2.5‰, in the rest of the Curonian Lagoon it is less than 0.5‰. The exchange flow showed vertical structure, but was horizontally uniform with the presence of a two-directional flow that from time to time changes to either saline water one-directional flow to the Curonian Lagoon or fresh water one-directional flow to the sea. Two-directional flow duration decreases with a distance from sea entrance in Klaipėda Strait from around 180 days yr−1 close to the sea entrance to 50 days yr−1 just behind Kiaulės Nugara island. One-directional outflow duration is increasing with a distance from the sea entrance from 100 to 225 days yr−1. One-directional inflow duration occurs in the range of 70–100 days yr−1. The analysis of the ratio of buoyancy layer thickness to water depth (hb/H) and the Wedderburn number identified the main importance of wind action on the flow structure. Strong winds from the North and NW determine a barotropic inflow which is mostly responsible for the salt water intrusion into the Curonian Lagoon. Absence of wind or cross-strait wind regimes allows the maintenance of a two-layer flow typical of estuarine dynamics.

Standing-up exerciser based on functional electrical stimulation and body weight relief - M. Ferrarin; E. E. Pavan; R. Spadone; R. Cardini; C. Frigo (Medical & Biological Engineering & Computing, 2002)